Kulturowo-religijny stosunek do bankowości a wielkie religie świata - Kurkliński, Lech (Annales. Etyka w Życiu Gospodarczym, 2015)
The article is dedicated to the attitude of the great world religions (Judaism, Christianity,Islam, Buddhism, Hinduism and Confucianism) to the world of finance, includingbanking. The issue of usury plays a key role together with the evolution ofethical aspects related to obtaining compensation for money lending. The analysisis focused on the other aspects of banking activities, such as saving, investing, andinstitutional development of the banking sector as well. The author underlines thefar-reaching convergence between religions in this area, in spite of the considerablevariation in historical and geographical conditions of their formation. The importanceof cultural (religious) differences, including the nuances or more fundamentalaspects, has a significant impact on bank management in different regions.For successful development, large multinational corporations have to take into considerationthe abovementioned circumstances, regardless of globalization processes.